Association between multidrug-resistant bacteria and outcomes in intensive care unit patients: a non-interventional study - Martins, Alessandro Pacheco Silveira; da Mata, Camila Pacheco Silveira Martins; dos Santos, Uener Ribeiro; de Araújo, César Augusto; Leite, Edna Marilea Meireiles; de Carvalho, Luciana Debortoli; Vidigal, Pedro Guatimosim; Vieira, Cristina Dutra; dos Santos-Key, Simone Gonçalves (Frontiers in Public Health, 2024)
Background: In intensive care units (ICUs), infections by multidrug-resistant (MDR) microorganisms should be monitored to prevent healthcare-associated infections (HAIs). Methods: From 2018 to 2020, we investigated all medical records of patients admitted to the ICU of a public university hospital. All patients colonized/infected by MDR microorganisms and submitted to active surveillance cultures (ASCs) were included. Results and Discussion: Male patients prevailed, and 9.5% were positive for MDR bacteria. In-hospital deaths were statistically significant (p < 0.05) for older patients, patients with orotracheal tube use during previous and current hospitalization, and patients with high blood pressure, cardiac and pulmonary diseases, and chronic kidney disease. Carbapenem resistant Enterobacteriaceae was the most frequently resistance profile, followed by extended-spectrum beta-lactamase. The diagnosis or evolution of HAIs was statistically significant (p < 0.0001) for patients treated with meropenem and vancomycin, and in-hospital deaths occurred in 29.5% of patients using polypeptides while the use of macrolides reduced the odds for mortality. The BRADEN Scale demonstrated that 50% of the patients were at high risk of dying. Conclusions: Patients hospitalized in the ICU, colonized or infected by MDR bacteria, using invasive medical devices, and with underlying medical conditions presented increased mortality rates. The prescription of meropenem and vancomycin should be carefully monitored once patients using these antimicrobials already have or develop an HAI.